EMBLEMATIC «MECHANISMS» AND THE THEORY OF SIGMUND FREUD - Солецький , О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The comparison between the emblematic «mechanisms» of signification and Freudian psychoanalytical theory has been studied in the paper. The Austrian psychiatrist discovered some patterns in mythological plots underlying the formation of his scientific terminology, methodology and classification of psycho-emotional behavioral types. Handling with the images of Eros and Thanatos, exploiting the mythological stories about Oedipus and Electra, Prometheus, Narcissus and lots of others to concretize behavioral complexes are indicative of the presence of «emblematic methodology» in developing psychoanalytical concepts and categories. His treatment of noted mythological plots comes to emblematic reduction.